Guided Inquiry Worksheets with Teaching Aids: Improving Students’ Scientific Literacy - Utami, Vina Bekti; Fitriani, Wulandari; Suhendar, Haris (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
This study aims to improve students' scientific literacy through the use of worksheet integrated with guided inquiry aided by teaching aids. This study used a Pre-Experimental design with a One-Group Pretest-posttest design conducted in 1 class. The subjects of the study were students of Phase D of MTSS Persis Cikalongkulon. Data collection techniques were pre-test and post-test (scientific literacy) and questionnaires. Worksheet-guided inquiry aided by teaching aids was declared very feasible by expert validators and practitioners (science teachers) and effective in improving students' scientific literacy with an N-Gain of 0.51 which is included in the moderate category. The practicality of worksheet has an average score of 35.87 out of a maximum total score of 48 and these results are in the good category. Based on the questionnaire of students' interest in learning, the results showed that 80% of students felt the learning atmosphere was more active and enjoyable.